A mercantilização do trabalho juvenil pela via dos contratos de aprendizagem - Marcelino, Cecília Paranhos Santos (2011)
This study aimed to investigate whether the largest youth employed under the special condition of apprentice workers have their rights guaranteed by the companies with the ability to reconcile work and school activities. To construct the theoretical framework on the subject was used as the foundation of the research theories of commodification of labor, focusing on Marxist ideas, continuing arguments about the flexibility and precariousness of the workforce by linking these ideas to work performed by adolescent learners in condition. In support of this theory, commodification, promoted a historical review of work done by children and adolescents, presenting factors for their existence and provides data about its current condition. The field research took shape qualitative, and was held at the SENAI-National Service of Industrial Education, along with five teenage apprentices and Coordinator of the SOE-Educational Guidance Service. The process of data analysis was divided into four stages, where initially traced to the socio-economic status of adolescents in student work, their working conditions, especially with regard to the nature of the tasks performed and the journey , about family relationships and social learners, and if teenagers can combine work and study. As a result of the analysis we obtained the removal of continued education of apprentices interviewed, the lack of union protection, the difficulty of training quality to the market, as well as suffering because of occupation of their time at work early age.